2012
DOI: 10.3390/ijms14010394
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthesis Is Increased in Cybrid Cells with m.3243A>G Mutation

Abstract: Nitric oxide (NO) is a free radical and a signaling molecule in several pathways, produced by nitric oxide synthase (NOS) from the conversion of l-arginine to citrulline. Supplementation of l-arginine has been used to treat MELAS (mitochondrial encephalopathy with lactic acidosis and stroke like syndrome), a mitochondrial disease caused by the m.3243A>G mutation. Low levels of serum arginine and endothelium dysfunction have been reported in MELAS and this treatment may increase NO in endothelial cells and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The DAF-FM compound was washed off the cells, and phenol red-and serum-free media was placed on the cells. Following incubation, fluorescent intensity was measured and compared between control (n ϭ 3 animals) and CDH (n ϭ 3 animals) cells as previously described (7,13,28). VEGF protein (25 ng/ml) was used as a positive control to stimulate NO production.…”
Section: Methodsmentioning
confidence: 99%
“…The DAF-FM compound was washed off the cells, and phenol red-and serum-free media was placed on the cells. Following incubation, fluorescent intensity was measured and compared between control (n ϭ 3 animals) and CDH (n ϭ 3 animals) cells as previously described (7,13,28). VEGF protein (25 ng/ml) was used as a positive control to stimulate NO production.…”
Section: Methodsmentioning
confidence: 99%
“…This down-regulation was only found in the presence of COX deficiency, as other patients with Complex II or I deficiency did not have alterations in NOS activity (99). However, these mechanisms may be more complex because a study with cultured osteosarcoma derived cybrid cells with a mitochondrial deficiency due to the m.3243A>G mutation, showed an increase of intracellular NO and nitrate/nitrite in cultured media when compared the control cells (107). On the other hand, another study with SH-SY5Y (neuroblastoma derived) cybrid cells, carrying the same mutation (m.3243A>G) showed a significant reduction of nitrite/nitrate concentration, which suggested that these cells had a reduced NOS activity (108).…”
Section: No Synthesis and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…It has been previously suggested that L-arginine supplementation in MELAS may work by enhancing nitric oxide mediated vasodilation of blood vessels with intrinsically impaired capacity for vasodilation [ 4 ]. A recent study found elevated baseline levels of intracellular nitric oxide in m.3243A>G cybrid cells, bringing into dispute the latter role of L-arginine supplementation and raising the possibility of an alternative metabolic role [ 30 ]. Our finding of improved aerobic metabolism supports a benefit from arginine supplementation beyond nitric oxide mediated vasodilation.…”
Section: Discussionmentioning
confidence: 99%